Hubungan Ketahanan dan Kerawanan Pangan dengan Social Capital dan Food Choice Rumah Tangga di kelurahan Kutowinangun Lor, Kecamatan Tingkir, Kota Salatiga - Geovani, Devin; Renyoet, Brigitte Sarah; Tauho, Kristiani Desimina (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Food security at this national level has received attention because it has not yet reached the word